Sociodemographic Risk Factors for Dermal Infections with Methi-cillin Sensitive and Methicillin Resistant Staphylococcus aureus among Sheep Breeders in Diyala Governorate , Iraq - Bressam Fajer, Zainab; Ibrahim Ali Al-Ezzy, Ali; H AL-Zuhairi , Ahmed (Diyala Journal of Medicine, 2023)
Background: Staphylococcus aureus is one of the dominant pathogen among skin infections in human and animals. Objective: To isolation and identification of S.aureus from sheep breeders by traditional method &Automated Vitek 2 system ,Detection of methicillin resistant gene (mecA) by conventional PCR. Evaluation of relationship between S.aureus in-fection and possible risk factors in human (age, sex, education level, economic statue, hospitalization in last four weeks contact with sheep skin lesions, and contact with pets). Patients and Methods: A total of 44 skin swaps collected from sheep breeders suffered from variety of infected skin lesions (wounds, abscesses, atopic dermatitis, acne, chronic skin diseases etc.) recording; sex, age, education level, economic statue, hospitaliza-tion in last four weeks, contact with sheep skin lesions, and contact with pets to detect S. aureus, MRSA and estimating the risk factors, by employing traditional laboratories methods in addition to confirmatory techniques by VETEK2 sys-tem and PCR, using specific primers (Staur 4, 6), MRSA gene primers (mecA). Results: Methicillin sensitive S. aureus was reported in 34.09% versus40% for MRSA among sheep breeders. Significant correlation reported between age groups and MRSA infections. Although, the rate of infection with methicillin sensitive S. aureus and MRSA was higher among males compared with females , no signifi-cant correlation reported between sex and infection with methicillin sensitive S. aureus and MRSA. Female breeders were at high risk for getting dermal MRSA infections compared with males. No significant correlation between the educa-tion level, economic status, contact with pets and methicillin sensitive S. aure-us , MRSA infections as Risk factors. Methicillin sensitive S. aureus infections among breeders significantly correlated with hospitalization in last four weeks .Significant correlation reported between contact with skin lesions of sheep and methicillin sensitive S. aureus , MRSA infections among breeders. Conclusion: Methicillin resistant trait was common among S.aureus isolated from sheep breeders .MRSA infections correlated with age. Female sheep breeders were at high risk for getting S.aureus and MRSA infections. Sex , education level, eco-nomic status, contact with pet play no role in infection with S.aureus. hospitali-zation in last four weeks, contact with skin lesions correlated significantly with S. aureus, MRSA infections among breeders.